2013
DOI: 10.1021/jp310229h
|View full text |Cite
|
Sign up to set email alerts
|

On the Azo/Hydrazo Equilibrium in Sudan I Azo Dye Derivatives

Abstract: In this study, Raman, infrared, UV/vis, NMR, and single crystal X-ray diffraction spectroscopies are used to elucidate the tautomeric equilibrium of azo dyes derived from 1-phenyl-azo-2-naphthol (Sudan I). A new crystallographic structure is described for Sudan I, revealing the presence of intramolecular hydrogen bonds and supramolecular interactions, such as the unconventional C-H···O hydrogen bond type, π-stacking, and charge-dipole interactions. All of these weak intermolecular interactions play a role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 41 publications
(46 reference statements)
3
29
0
Order By: Relevance
“…The Sudan I molecules may mainly be protonated at multiple position, including the oxygen atom and two azo nitrogen atoms (N1 and N2), because they are the basic sites in the molecule. Furthermore, considering that Sudan I exists as a mixture of tautomers that is referred to as the azo (OH) and the hydrazone (NH) form, see Figure , protonation may occur at different sites for two kinds of Sudan I tautomers resulting in six different possible forms of protonated Sudan I molecule (MH‐1 to MH‐6). To identify the most favorable protonation site, the molecular electrostatic potential map (MEP) of Sudan I in azo and hyrdrazone form, and the proton affinity (PA) were calculated for six possible protonated forms of Sudan I molecule [M+H] + , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Sudan I molecules may mainly be protonated at multiple position, including the oxygen atom and two azo nitrogen atoms (N1 and N2), because they are the basic sites in the molecule. Furthermore, considering that Sudan I exists as a mixture of tautomers that is referred to as the azo (OH) and the hydrazone (NH) form, see Figure , protonation may occur at different sites for two kinds of Sudan I tautomers resulting in six different possible forms of protonated Sudan I molecule (MH‐1 to MH‐6). To identify the most favorable protonation site, the molecular electrostatic potential map (MEP) of Sudan I in azo and hyrdrazone form, and the proton affinity (PA) were calculated for six possible protonated forms of Sudan I molecule [M+H] + , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we have shown [3] by theoretical calculations and by analysis of the existing crystallographic data of structurally similar compounds [4][5][6][7][8] that the structures of the enol and keto tautomers of 4-((2-hydroxynaphthalen-1-yl)diazenyl)-3,5-dinitrobenzoic acid as previously predicted by Adegoke are incorrect. In the same study [3] the tautomerism of 1-((2nitrophenyl)diazenyl)naphthalen-2-ol (1, Scheme 1) was investigated by using DFT calculations and UV-Vis spectroscopy.…”
Section: Introductionmentioning
confidence: 88%
“…S2 and S3 in the ESI). The phase analysis revealed that Sudan I consists of 82% of the polymorph I (Oliveri et al 1989), 8% of the polymorph II (Liu et al 1997), and 10% of the polymorph III (Ferreira et al 2013), whereas 4-methylumbelliferone exists in the anhydrous form (Panini et al 2014). …”
Section: Powder X-ray Diffractionmentioning
confidence: 99%